1997
DOI: 10.1111/j.1365-2222.1997.tb01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced sputum to assess airway inflammation: a study of reproducibility

Abstract: The importance of this study is the confirmation, within important statistical guidelines for a study of reproducibility, that the methods examined are reproducible and valid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
58
3
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 18 publications
9
58
3
3
Order By: Relevance
“…In healthy volunteers the reproducibility of total cell count was high as well as that of eosinophils, neutrophils and macrophages. Consistent with previous studies the lymphocyte count was not reproducible [17]. The fairly small amount of saline used in the experimental procedure to limit the inhalation time and to avoid the dilution of samples also enabled the measurements of cytokines in induced sputum.…”
Section: Discussionsupporting
confidence: 64%
“…In healthy volunteers the reproducibility of total cell count was high as well as that of eosinophils, neutrophils and macrophages. Consistent with previous studies the lymphocyte count was not reproducible [17]. The fairly small amount of saline used in the experimental procedure to limit the inhalation time and to avoid the dilution of samples also enabled the measurements of cytokines in induced sputum.…”
Section: Discussionsupporting
confidence: 64%
“…In line with these observations, FORESI et al [15] have recently demonstrated that a significant number of eosinophils and metachromatic cells may be present in induced sputum from subjects with seasonal allergic rhinitis. However, their findings are at variance with those of PIN et al [20] and SPANEVELLO et al [21], who failed to show a significant difference in the percentage of eosinophils in induced sputum between individuals with seasonal allergic rhinitis (studied out of the pollen season) and healthy controls. The reasons for such discrepancies might be related to diversity in the disease activity in the subjects studied or to important differences in methodology and study protocol.…”
Section: Discussioncontrasting
confidence: 56%
“…Although unusual, this finding has previously been reported in other papers 37 and many reports have described that the lymphocyte counts are poorly reproducible. 38,39 In conclusion, our results indicate that induced sputum cells collected from asthmatics displayed an increased transcription for MMP-1 and TIMP-1. This excessive transcription of matrix metalloprotease may significantly contribute to airway remodelling in asthma and suggest applying an animal model of asthma to human MMP-1 expressing transgenic mice 40 in order to investigate the precise effects of MMP-1 overexpression on the bronchial wall extracellular matrix composition in the context of a repeated allergen exposure.…”
Section: Discussionmentioning
confidence: 58%